An introduction to the green economy: science, systems and sustainability - Newton, Adrian C.; Cantarello, Elena (Abingdon, 2014)
"The green economy is widely seen as a potential solution to current global economic and environmental crises, and a potential mechanism by which sustainable development might be achieved in practice. Considerable investments are now being made into the development of green technology, renewable energy, biodiversity conservation, resource efficiency, recycling of materials and green infrastructure. This textbook provides a comprehensive introduction to the green economy, using a strongly interdisciplinary approach based on environmental science, rather than treating it as a sub-set of economics. The scientific principles of sustainability are presented, which provide the foundations of the green economy, with a particular focus on systems-based approaches. Examples of real-world case studies are used to illustrate how the green economy can be achieved in practice. In this way, the authors provide a thorough overview of both the principles and practice of the green economy, drawing from a wide range of disciplines including ecology, geography, social science, psychology, sustainability science, environmental science, law and economics. The emphasis is on presenting results of the latest research, derived from leading scientific journals. Rather than focusing on a single definition of what constitutes a ‘green economy’, the book introduces readers to the diversity of opinion that exists, and engages them in what is an active, on-going debate. This reflects the fact that many aspects of the green economy, and sustainable development more generally, are currently contested. In particular, the book will help readers to strengthen their ability to critically evaluate the evidence for and against the views presented, and to actively contribute to the future development of the green economy."